2023
DOI: 10.3389/fimmu.2023.1105399
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and predictive values of pyroptosis-related genes in sepsis

Abstract: BackgroundSepsis is an organ dysfunction syndrome caused by the body’s dysregulated response to infection. Yet, due to the heterogeneity of this disease process, the diagnosis and definition of sepsis is a critical issue in clinical work. Existing methods for early diagnosis of sepsis have low specificity.AimsThis study evaluated the diagnostic and predictive values of pyroptosis-related genes in normal and sepsis patients and their role in the immune microenvironment using multiple bioinformatics analyses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…We also looked at the connection between this diagnostic model and immune cell infiltration and discovered that the two were closely related. This is because cellular immune regulation involving immune cells plays There is an undeniable similarity between our study and the earlier ones [14][15][16][17] in that both used various highthroughput sequencing data from pediatric sepsis, both used machine learning to find diagnostic genes and finally screened for two common genes (CD177 and MMP8) that can accurately diagnose pediatric sepsis. However, our study still has several strengths.…”
Section: Discussionmentioning
confidence: 89%
“…We also looked at the connection between this diagnostic model and immune cell infiltration and discovered that the two were closely related. This is because cellular immune regulation involving immune cells plays There is an undeniable similarity between our study and the earlier ones [14][15][16][17] in that both used various highthroughput sequencing data from pediatric sepsis, both used machine learning to find diagnostic genes and finally screened for two common genes (CD177 and MMP8) that can accurately diagnose pediatric sepsis. However, our study still has several strengths.…”
Section: Discussionmentioning
confidence: 89%
“… 45 , 46 Notably, recent research has increasingly focused on the influence of STAT3 on the progression of different diseases through the regulation of cell death, including sepsis and lung injury. 47 , 48 Additionally, certain studies have demonstrated that p-STAT3 facilitates the acetylation of histone H3 and H4 on the NLRP3 promoter, as well as the activation of the NLRP3 inflammasome, which may be directly regulated by p-STAT3. 48 Furthermore, several studies have demonstrated the impact of STAT3 on pyroptosis through its influence on other targets, including AIM2 and GSDME.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the utilization of diverse high-throughput sequencing data from pediatric sepsis and the application of machine learning techniques to identify characteristic genes, our study presents distinct advantages compared to previous investigations. 17,23,24 Firstly, our diagnostic model exhibits enhanced diagnostic efficacy, as evidenced by its successful application to clinical samples and subsequent validation using three publicly available datasets. Secondly, our developed diagnostic model demonstrates effectiveness in distinguishing between bacterial and non-bacterial etiologies of pediatric sepsis (AUC=0.82).…”
Section: Discussionmentioning
confidence: 99%